2020
DOI: 10.21203/rs.2.22825/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining abbreviated literature searches with single-reviewer screening: three case studies of rapid reviews

Abstract: Background Decision-makers increasingly request rapid answers to clinical or public health questions. To save time, personnel, and financial resources, rapid reviews streamline the methodological steps of the systematic review process. We aimed to explore the validity of a rapid review approach that combines a substantially abbreviated literature search with single-reviewer screening of abstracts and full texts using three case studies. Methods We used a convenience sample of three ongoing Cochrane reviews as … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In a case study, this approach reduced the number of abstracts that needed to be screened by up to 90 percent without missing studies that would have changed conclusions. 20 It is conceivable that such a targeted literature search approach could improve the performance of semi-automated screening tools because they would have to deal with less noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case study, this approach reduced the number of abstracts that needed to be screened by up to 90 percent without missing studies that would have changed conclusions. 20 It is conceivable that such a targeted literature search approach could improve the performance of semi-automated screening tools because they would have to deal with less noise.…”
Section: Discussionmentioning
confidence: 99%
“…18 Natural language processing technology: A semantic technology process that is used to normalize variants (e.g., different conjugations of a verb) of a single concept, and to identify complex concepts (e.g., terms made up of several words) in a text. 19,20 Prediction: A forecast of whether a record is relevant (include) or irrelevant (exclude) for a given systematic review. Semi-automated screening/text mining tool: Any Web-based application that employs a combination of text mining and text classification to assist systematic reviewers to make decisions during the title and abstract screening process.…”
Section: General Terms Of Machine Learningmentioning
confidence: 99%
“…71 Although consensus exists that methodological shortcuts in the conduct of a review can lead to bias, retrospective comparisons of systematic reviews and RRs indicate that both types of reviews apparently lead to comparable conclusions. Affengruber et al 72 found that, when compared to Cochrane reviews, a RR approach that combines abbreviated literature searches and singlereviewer abstract screening had low accuracy. However, this seems to depend on the research area.…”
Section: Discussionmentioning
confidence: 99%
“…The RR approach would have led to comparable conclusions as the original Cochrane review for oncological topics, but not for public health topics. 72 Furthermore, the varying quality of systematic reviews has to be taken into account, hampering the identification of marked differences between the RRs and systematic reviews in general. 73 For example, in an analysis of the methodological restrictions of RRs compared to systematic reviews, a duplicate study selection and data extraction was only performed in 37% of reviews labeled as "systematic."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation